2021
DOI: 10.3389/feduc.2021.655747
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Differences in the Canonical and the Reverse Distance Effect and Their Selective Association With Arithmetic and Mathematical Competencies

Abstract: Understanding the relationship between symbolic numerical abilities and individual differences in mathematical competencies has become a central research endeavor in the last years. Evidence on this foundational relationship is often based on two behavioral signatures of numerical magnitude and numerical order processing: the canonical and the reverse distance effect. The former indicates faster reaction times for the comparison of numerals that are far in distance (e.g., 2 8) compared to numerals that are clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…It is plausible to assume that group differences in symbolic number processing ability might be observed when more fine-grained indices of the symbolic magnitude processing and order processing are considered, i.e., the canonical numerical distance effect and the reversed distance effect, respectively. Performance on a numerical magnitude compari son task is poorer (i.e., slower reaction times) for numbers that are closer together (e.g., 5 and 6) compared to numbers further apart (e.g., 2 and 7), which is the classic numerical distance effect (Vogel et al, 2021). It has been posited that smaller numerical distance effects are reflective of more precise representations of the number representation system (e.g., Schwenk et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible to assume that group differences in symbolic number processing ability might be observed when more fine-grained indices of the symbolic magnitude processing and order processing are considered, i.e., the canonical numerical distance effect and the reversed distance effect, respectively. Performance on a numerical magnitude compari son task is poorer (i.e., slower reaction times) for numbers that are closer together (e.g., 5 and 6) compared to numbers further apart (e.g., 2 and 7), which is the classic numerical distance effect (Vogel et al, 2021). It has been posited that smaller numerical distance effects are reflective of more precise representations of the number representation system (e.g., Schwenk et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been posited that smaller numerical distance effects are reflective of more precise representations of the number representation system (e.g., Schwenk et al, 2017). A reverse distance effect is often reported for the numerical order task (Vogel et al, 2021), where participants are often faster when the distance between the three in-order numbers is small (3 4 5) compared to when the distance is large (2 4 6). Interestingly, a very recent study by Hohol et al (2020) examined whether professional mathematicians showed a smaller canonical numerical distance effect as compared to engineers, social scientists, and a reference group from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns similar to the priming DEs (i.e., faster performance with small compared to large numerical distances) arise also in tasks that focus on the ordinal property of numbers, such as the relative order judgment task (requiring participants to judge whether the order in number pairs is ascending or descending; e.g., Turconi et al, 2006) or the number order verification task (requiring participants to verify the correctness of order in number pairs or triplets; e.g., Franklin et al, 2009;Lyons & Beilock, 2011). The emerging effect, known as reverse DE, although present both in children (Lyons & Ansari, 2015;Vogel et al, 2015) and in adults (Vogel et al, 2017(Vogel et al, , 2019, is more variable across individuals when compared to the comparison DE, possibly due to the involvement of multiple individual strategies, such as long-term memory retrieval and sequential-procedural comparisons (Vogel et al, 2021). Notably, all the above-mentioned methods except Holyoak's (1978) study assessed the DE implicitly, that is, without explicit processing of the numerical distance between the presented numbers.…”
Section: Variants Of the Dementioning
confidence: 99%
“…In contrast, Orrantia et al (2019) highlight the extensive overlap between cardinal (number comparisons) and ordinal processing (order judgements) in adults’ arithmetic, suggesting that both processes draw on underlying symbolic magnitude associations. Other researchers have suggested that both familiarity and magnitude associations may influence performance on the order judgement task, depending on the task demands (e.g., stimulus characteristics; Vos et al, 2021) and individuals’ strategy use (Dubinkina et al, 2021; Muñez et al, 2021; Vogel et al, 2021; Vos et al, 2021). Extending the latter views, strong correlations between order judgements and arithmetic may reflect the extent to which individuals have developed an integrated knowledge system (Xu et al, 2019).…”
Section: Fundamental Numeracymentioning
confidence: 99%